Greenhouse gas production and lipid biomarker distribution in Yedoma and Alas thermokarst lake sediments in Eastern Siberia. (28th March 2021) - Jongejans, Loeka L.; Liebner, Susanne; Knoblauch, Christian; Mangelsdorf, Kai; Ulrich, Mathias; Grosse, Guido; Tanski, George; Fedorov, Alexander N.; Konstantinov, Pavel Ya.; Windirsch, Torben; Wiedmann, Julia; Strauss, Jens
Abstract: Permafrost thaw leads to thermokarst lake formation and talik growth tens of meters deep, enabling microbial decomposition of formerly frozen organic matter (OM). We analyzed two 17‐m‐long thermokarst lake sediment cores taken in Central Yakutia, Russia. One core was from an Alas lake in a Holocene thermokarst basin that underwent multiple lake generations, and the second core from a young Yedoma upland lake (formed 70 years ago) whose sediments have thawed for the first time since deposition. This comparison provides a glance into OM fate in thawing Yedoma deposits. We analyzed total organic carbon (TOC) and dissolved organic carbon (DOC) content, n ‐alkane concentrations, and bacterial and archaeal membrane markers. Furthermore, we conducted 1‐year‐long incubations (4°C, dark) and measured anaerobic carbon dioxide (CO2 ) and methane (CH4 ) production. The sediments from both cores contained little TOC (0.7 ± 0.4 wt%), but DOC values were relatively high, with the highest values in the frozen Yedoma lake sediments (1620 mg L −1 ). Cumulative greenhouse gas (GHG) production after 1 year was highest in the Yedoma lake sediments (226 ± 212 µg CO2 ‐C g −1 dw, 28 ± 36 µg CH4 ‐C g −1 dw) and 3 and 1.5 times lower in the Alas lake sediments, respectively (75 ± 76 µg CO2 ‐C g −1 dw, 19 ± 29 µg CH4 ‐C g −1 dw). The highest CO2 production in the frozen Yedoma lake sediments likely results from decomposition of readily bioavailable OM, while highest CH4 production in the non‐frozen top sediments of this core suggests that methanogenic communities established upon thaw. The lower GHG production in the non‐frozen Alas lake sediments resulted from advanced OM decomposition during Holocene talik development. Furthermore, we found that drivers of CO2 and CH4 production differ following thaw. Our results suggest that GHG production from TOC‐poor mineral deposits, which are widespread throughout the Arctic, can be substantial. Therefore, our novel data are relevant for vast ice‐rich permafrost deposits vulnerable to thermokarst formation. Abstract : Ongoing climate change leads to permafrost thaw, thermokarst lake formation, and talik growth. This enables microbes to decompose the thawed organic matter. We measured greenhouse gas (GHG) production, n ‐alkanes and lipid biomarkers in thawed sediments and permafrost underneath thermokarst lakes in Central Yakutia, Russia. We found that GHG production is higher in Yedoma lake sediments compared to Alas lake sediments. Even in organic carbon‐poor sediments, GHG production was substantial. Our results show that drivers for anaerobic CO2 and CH4 production differ. Our novel data are relevant for vast ice‐rich permafrost deposits vulnerable to thermokarst formation.